IMPLEMENTATION OF NEW PUBLIC MANAGEMENT IN WORLD AND NATIONAL PRACTICE OF PUBLIC ADMINISTRATION - Kukhareva G.P. (Pressing Problems of Public Administration, 2015)
The analysis of New Public Management, including main aspects, aims, principals and characteristics, has been done. Advantages, disadvantages and problems connected with the concept implementation are discovered. The main questions related to possible implementation of New Public Management in Ukraine has been designated.